'Until it kills you': cancer related stigma on the Chilean tobacco packaging warning messages 2014-2016 campaign. Issue 4 (4th July 2019) - Fernández González, Loreto; Diaz-Castrillón, Fernanda
ABSTRACT: Chile has one of the highest rates of tobacco consumption in the Americas and lung cancer is the main cancer-related death cause in the country. Since 2006, the Chilean Ministry of Health mandates pictorial warning labels on all tobacco packaging, in line with global trends of tobacco control and anti-smoking policy. The aim of this study was to perform a discourse analysis (DA) of the Chilean Campaign in force during 2014–2016. Focusing on what the campaign promotes, we problematized its discursive effects, in relation to lung cancer, cancer treatments and the causality between smoking and lung cancer. We developed an analytical inductive process based on Santander's DA model, assessing written and visual rhetoric, extracting a core axis of the inevitable temporal progression of disease throughout the labelling messages story line, from the viewpoint of stigma as a discrediting trait. Main axis of analysis included: rhetoric of written and visual elements, fear & disgust appeal, and intertextuality with religious/military discourses. The campaign posits a metaphorical equivalence among smoking and lung cancer, and the latter as an inevitably fatal disease: 'until it kills you'. Lung cancer is a discrediting feature implying physical and moral deterioration, due to aggressive treatments and personal identity spoiling. Fear and disgust appeals are strongly used through images and colors. The campaign's rhetoric interpellates to 'choose' between life and death, showing lung cancer as a self-inflicted disease. We problematize the ethical/moral implications of public health campaigns based on reinforcing stigmatization of cancer patients and therapeutic nihilism.